The study of the experience of captivity in Iran-Iraq war: The investigation of “I am alive” and “Winter narrative” novels based on qualitative content analysis - M. Tabiee; M. Hashempour Sadeghian; A. Hooshiar (Taḥqīqāt-i Farhangī-i Īrān)
Global military aggression against the Iraqi regime of land, air and sea to the Islamic Republic of Iran on 31 September 1359, is an important event that its consequences is critical for the present and future generations. One of the consequences of most of wars, including the Iran-Iraq war, is captivity. This paper aims to evaluate this aspect of eight-year war between Iran and Iraq. This paper from the point of view of women’s experiences and men’s experiences of captivity. In this regard, using qualitative content analysis based on customary approach, two sets of memories of captivity named “I am alive” –Masoume Abad’s captivity memory- and named “wnter narrative”-Hosein Paimardi’s captivity memory- has examined and in this way, extracted concepts, sub-categorise and main categories. This paper’s conclusions show that captivity is defined as resistance and struggle to Iranian captives. But in particular, the experiences of these men and women is divided under 16 sub-categorises and these are defined under 6 main categorises that include: Conflict place, violence, complications, psychological experiences, mechanisms to deal with crisis and hostile policies.